SOME ASPECTS OF BREEDING PROGRAMS OF PEA (PISUM SATIVUM) - S. V. Goncharov; A. V. Titarenko; N. A. Korobova (Зерновое хозяйство России, 2018)
In 2012-2013 pea was cultivated on the areas of 1.282 th. ha and 1.140 th. ha respectively. Pea took  about 2% of  lands, which was really less than a recommended share. In 2013 the largest areas were in Stavropolsky Krai (137 th.ha), Altaisky Krai (112 th.ha) and Rostov region (99 th.ha). From 118 varieties included into the State Register of breeding achievements and approved to use in RF in 2014 there were only 33% of relatively young (5 years) varieties and 21,2% of rather old ones (more than 16 years). The term of variety change in Russia is 16-17 years, but in Ukraine it’s 11 years. Too long periods of variety change is considered to be one of the reasons of decrease of plant protein production.  From 2003 the varieties of foreign breeding were included into the State Register of breeding achievements of RF and in 2014 there were 12,7% of total number of pea varieties. Being not more productive than domestic varieties, foreign cultivars have commercial success due to successful variety strategy and stable seed-growing. In agricultural production the varieties with wide adaptability and good qualitative traits are more demanded and preferred. The article tells about efficient working institutions and gives accounts of market volume of seeds.